Complex segregation analysis of familial amyloidosis in Oriental shorthair cats. (November 2020) - Struck, A.K.; Klotz, D.; Hülskötter, K.; Wohlsein, P.; Schmitz, J.; Bräsen, J.H.; Distl, O.
Highlights: Amyloidosis is a genetic condition in Oriental shorthair cats. Amyloid accumulated predominantly in the liver and thyroid gland. Immunostaining with specific antibodies identified amyloid A protein. Complex segregation analyses showed a complex inheritance for amyloidosis. Abstract: Amyloidosis in Siamese/Oriental cats is a lethal condition with variable age of clinical onset. There is no sex predisposition and clinical signs of disease usually become apparent by 1–7 years of age. In the terminal stages, the liver is enlarged and pale, and contains parenchymal hemorrhages. In the present study, pedigree data from 17 cats with clinical signs consistent with amyloidosis underwent genetic analysis. Necropsy and histopathological data were available for 10 of the 17 cats. Necropsy findings included pale, fragile and enlarged livers with capsular ruptures and parenchymal hemorrhages, and sanguineous effusions in the abdominal cavity. Congo red staining with birefringence confirmed systemic amyloidosis mostly involving the liver and thyroid gland. In four of the 10 cases, protein deposits were classified as amyloid A protein (AA-amyloid) by immunostaining. Pedigree data for all 17 affected cats indicated a familial trait. Animal threshold model analysis demonstrated that the heritability for amyloidosis was 0.56 ± 0.09 (standard error). Complex segregation analysis was used for statistical comparisons among models to determine environmental or sex dependent effects, and Mendelian, polygenic, or mixed Mendelian and polygenic inheritance patterns. A mixed model with a Mendelian and polygenic component provided the best fit to the data and thus was most likely. All other models of inheritance were rejected due to their insufficient ability to explain segregation of amyloidosis. In conclusion, we found evidence for a complex genetic basis for amyloidosis in Oriental shorthair cats.